FESTIVALS, COMMUNICATION AND DEVELOPMENT - Jeyaraj, Jesudason Baskar (Journal of Dharma, 2003)
Communities around the world have their own religious, political and cultural festivals and celebrate them in their own style on a particular period of time in a year. Religious communities in India whether they belong to Hinduism or Islam or Christianity or other faiths love to celebrate festivals with elaborate and expensive arrangements to make their celebrations grandeur. Some of the festivals such as Deepavali, Ramzan, Christmas are celebrated nation-wide by the respective communities with the greetings and blessings of their religious leaders, politicians of different parties and the President of India. Some other festivals such as Onam of Kerala and Pongal of Tamil Nadu are celebrated at the state level. A number of regional festivals are celebrated by the villagers or a sect or caste group or a tribe. Chithirai festival, marking the beginning of Tamil New Year is a grand festival celebrated locally for a week in the Meenakshi Temple at Madurai. National festivals such as Independence Day, Republic Day and May Day are remembered by all the communities of India, irrespective of their caste and religion. Festivals are given so much of importance in Indian society because they function as a medium of communication enabling the communities to maintain their self-identity in the midst of pluralistic culture. Festivals remind them of their religious, historical and social traditions. They strengthen the social and religious bond of the communities. Festivals make their worship more meaningful and contribute to their spirituality. Festivals of historical importance remind the participants of their historical past and motivate to shape their future. However, festivals are used sometimes to oppress a certain section of the community either a sub-caste or women or children.